Review of critical thinking skills in physics: evaluation and learning in high school - Y Resmawati; P Sinaga (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2021)
As stated in the Partnership for 21st Century Learning (P21), learning skills and innovation are needed to prepare students to cope with increasingly complex lives supported by a variety of skills, including critical thinking skills. Critical thinking skills is a reflective process in analysing and evaluating information to determine one's beliefs and self-behaviour that can be developed through flexible, original, and precise creative processes. Critical thinking skills need to be taught and evaluated with suitable methods and strategies. For this reason, it is necessary to study in advance what methods have been used by previous researchers or find best practices in learning to improve critical thinking skills. This article aims to describe empirically and theoretically related methods and learning of critical thinking skills in high school physics learning in Indonesia and report on best practices